2014
DOI: 10.2460/javma.244.11.1298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated blood donations on iron status and hematologic variables of canine blood donors

Abstract: All blood donation regimens induced a bone marrow regenerative response, which was able to restore depleted blood cells within 10 days after blood donation while maintaining iron status within the calculated reference range. However, dogs donating 13% of TBV every 2 months had a significant decrease in iron stores, which suggested that iron-related variables must be monitored during prolonged blood donor programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Baseline MCF ex‐TEM was significantly lower in the LRS treatment group compared to controls (62 ± 2.4 versus 57.8 ± 4.7 mm, P = 0.01), and this difference could have biased subsequent comparisons between the LRS treatment and the other treatment groups. Although this difference could suggest that the washout intervals between experiments that involved hemorrhage and VR (8 weeks) might not have been long enough to completely eliminate a carryover effect, this interval far exceeds the period required by the bone marrow to restore the depleted cells after blood donation in dogs (10 days) . The difference in MCT ex‐TEM was relatively small and might have been caused by type II error.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline MCF ex‐TEM was significantly lower in the LRS treatment group compared to controls (62 ± 2.4 versus 57.8 ± 4.7 mm, P = 0.01), and this difference could have biased subsequent comparisons between the LRS treatment and the other treatment groups. Although this difference could suggest that the washout intervals between experiments that involved hemorrhage and VR (8 weeks) might not have been long enough to completely eliminate a carryover effect, this interval far exceeds the period required by the bone marrow to restore the depleted cells after blood donation in dogs (10 days) . The difference in MCT ex‐TEM was relatively small and might have been caused by type II error.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, traditional markers of iron deficiency (including MCV, serum ferritin, and serum iron) were not different between the donor and control groups. Although both previous studies examining iron status in blood donor dogs have reported changes suggesting iron deficiency,14, 15 our study uses RBC and reticulocyte indices support the diagnosis of iron deficiency and IDE.…”
Section: Discussionmentioning
confidence: 78%
“…Depleted blood cells can be restored within 10 days of donation,15 suggesting that the interval between donations is adequate. However, repeated donation leading to IDE might permit only a blunted regenerative response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult RIs are representative when the population they refer to is composed of healthy subjects [ 30 ], and the use of a blood donor database can ensure this prerogative, since hematology and clinical biochemistry present a fundamental support to evaluate the health status of blood donors in a Veterinary Blood Bank [ 5 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%